Islamic Based Decision Making Strategies for Students Career Choices - Siddik, Muhammad; Haikal, Muhammad Fachran (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Many students, especially at the vocational high school level, often face difficulties in making the right career decisions. Lack of adequate information, limited social support, and lack of practical experience are the main challenges. These issues often lead to confusion in choosing a career path that aligns with students' potential and interests. This study aims to explore career decision-making strategies among 12th-grade students at Apipsu Pharmacy Vocational High School in Medan. With the increasing challenges in career selection, it is important for students to have access to adequate skills, information, and social support. Through observation and interviews, this study identified eight types of decision-making strategies, which were divided into effective and ineffective categories. The results showed that hands-on practices such as internships and industrial visits significantly increased students' motivation and understanding of available career options. Additionally, career guidance support was found to be crucial in helping students make decisions aligned with their potential and aspirations. The implications of this study suggest that experience-based learning and continuous career guidance support can significantly improve students' career decisions, reduce confusion, and enhance their readiness to face professional challenges.